Utilization of Coconut Dregs Waste into Zwieback Products - Lumoindong, Frans; Mamuaja, Christine F. (Pascasarjana Unsrat, 2017)
Study of coconut dregs waste utilization into zwieback products was carried out. This study was aimed to make zwieback products and to obtain the formula of coconut dregs waste utilization in zwieback products preferred by panelists. The study used a complete randomized design. The zwieback product had the treatment of coconut dregs waste addition respectively with A (0%), B (25%), C (50%), D (75%), E (100%). Results showed that the treatment of coconut dregs waste addition was 50%.Keywords: coconut dregs, waste utilization, zwieback